Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4093/dmj.2014.38.5.366
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Livingstone Potato (Plectranthus esculenthusN.E.Br) on Diabetes and Its Complications in Streptozotocin Induced Diabetes in Rats

Abstract: BackgroundThe effect of livingstone potato (Plectranthus esculenthus N.E.Br) on diabetes and its complications in Streptozotocin induced diabetic rats was investigated. The duration of the experiment was 4 weeks.MethodsThe blood glucose level of the rats was measured with a glucometer, the protein and glucose and specific gravity in the urine samples of the rats were measured using urine assay strips and urinometer respectively. The liver and kidney function parameters in the serum of the rats were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…Furthermore, the mechanism of action of alloxan has been widely studied [ 61 ]. These findings are in line with other studies that have shown that the treated groups had a lower overall area under the curve than the DC group when using blood glucose concentration as a routine and significant biological measure to determine how well a patientā€™s condition is improving while receiving diabetes therapy [ 62 ].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the mechanism of action of alloxan has been widely studied [ 61 ]. These findings are in line with other studies that have shown that the treated groups had a lower overall area under the curve than the DC group when using blood glucose concentration as a routine and significant biological measure to determine how well a patientā€™s condition is improving while receiving diabetes therapy [ 62 ].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the level of change in the body weight of experimental rats before and after treatment was compared. Weight loss is one of the major syndromes associated with diabetes, probably due to muscle wasting [ 57 ]. In our study, the diabetic-induced rat group (DC) showed significant weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Hispidulin-treated diabetic mice had higher islet mass than that of vehicle-treated mice, although the difference was not statistically significant (p = 0.08). As STZ induces diabetes by selectively destroying -cells, [35] we evaluated whether hispidulin treatment improved -cell survival by performing double immunolabeling of insulin and the activated caspase-3, a key protease involved in the terminal steps of cell apoptosis. Consistently, .…”
Section: Hispidulin Improves Pancreatic -Cell Survival In Diabetic Micementioning
confidence: 99%